Problematic of Teacher in Implementation of Curriculum 2013 on Learning Social Science Integrated SMP in Gowa District - Kurniawan, Rezki; Zhiddiq, Sulaiman; Maddatuang, Maddatuang (Universitas Negeri Makassar, 2018)
This research aims to determine: 1) Form of implementation of Curriculum 2013. 2) Problematic of teacher in implementation of Curriculum 2013. 3) Efforts made to overcome problematic of teacher in implementation of Curriculum 2013. Collecting data in this research using observation techniques, interview and documentation, and analyzed using qualitative descriptive analysis techniques. Result showed that: 1) Implementation of Curriculum 2013 with competence graduates covering aspects of attitudes, knowledge, and skills; using the student-oriented learning process, applying scientific approach. 2) In process of implementing curriculum in 2013 there are still many problems experienced teachers such as; curriculum changes in lesson plans; lack understanding function lesson plans; lack computers control develop lesson plans; lack preparation time in design lesson plans; social studies material presented integrated; distribution school books is not equitable; learning materials source limited; student worksheet function is not maximized; facilities learning media limited; lack mastery computer learning media; there are difficult in authentic assessment; format change in report book; social studies integrated textbooks still lack in library; computer laboratory not functionalized; lack extra facilities in class. 3) Efforts are being made to overcome the problematic of teachers, transform thoughts to mindset Curriculum 2013; seek school headmaster more attention and motivate teachers; followed socialization and training related Curriculum 2013 even harder; improve socialization relationships among teachers; self motivate to be passionate; utilizing resources reference books as well possible; studying computer science and information technology; and pursue school to provide and improve infrastructure and facilities to support learning process.